2020
DOI: 10.7759/cureus.11822
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Modern Social Media on Dermatologist Selection by Patients

Abstract: Social media have become the platform of choice for people seeking immediate access to information. They have become so ubiquitous and pervasive that many people are using them to research health care providers and communicate with them about their issues. This study looks into this phenomenon, focusing on how it affects people's thinking when deciding which doctor to see for skin-related concerns. Methodology A cross-sectional study was conducted among patients at Derma Clinic in Riyadh, Saudi Arabia. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In a study conducted among patients at Derma Clinic in Riyadh, Saudi Arabia, it was found that the number of participants who knew about their dermatologists from social media (Twitter, Instagram, Snapchat, Facebook, and Telegram) was 9.7 times higher than those who knew them from traditional sources (newspaper, radio, and TV) [2]. Another study conducted among Indonesian men found that consumers considered skincare brand advertisements that they have seen on social media more trustworthy [40].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In a study conducted among patients at Derma Clinic in Riyadh, Saudi Arabia, it was found that the number of participants who knew about their dermatologists from social media (Twitter, Instagram, Snapchat, Facebook, and Telegram) was 9.7 times higher than those who knew them from traditional sources (newspaper, radio, and TV) [2]. Another study conducted among Indonesian men found that consumers considered skincare brand advertisements that they have seen on social media more trustworthy [40].…”
mentioning
confidence: 99%
“…As per the results of the study conducted among patients at Derma Clinic mentioned previously, those who used social media to choose and follow their doctors favored Twitter. Of the social media users analyzed, patients who visited dermatology clinics for medical reasons preferred Twitter while those that visited for cosmetic purposes preferred Instagram to follow their doctors; which is understandable given that Instagram enables its users to showcase their looks, thus influencing others to also try aesthetic dermatology, a visual field [2]. With continued technological evolution, organizations that fail to recognize the prospects provided by social networking sites risk becoming marginalized by their inability to assimilate to social media as an expected form of communication.…”
mentioning
confidence: 99%
See 3 more Smart Citations